REPRESENTATIONS OF RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND HEALTH OF PUBLIC SERVANTS - Jerusa Mônica de Abreu Souza; Rafael da Silva Mattos; José Silvio de Oliveira Barbosa; Maria Lúcia Cavalieri; Renata Costa de Oliveira; Madel Therezinha Luz (Universidade Estadual do Oeste do Paraná, 2014)
The purpose of this study was to identify, from the theoretical and methodological references of the social representations, perceptions and ways of expressions of the relationship between physical activity and health, using 11 students involved in the Physical Activity and Health Promotion Project to Servants of University of the State of Rio de Janeiro. We seek to relate these perceptions, representations, and ways of expressions with dimensions of the concept of health. Using qualitative methodological approach, the data collection was conducted through semi-structured interview and drawings. The data was classified in topics (dimensions of the concept of health). We concluded that all respondents perceive the relationship between physical exercise and health in a positive way, especially the improvement of physical endurance, showed by a better performance on their daily activities. Furthermore, other dimensions of this relationship were also perceived in their speeches during the interviews, such as social, emotional, professional and intellectual dimensions.